Хос хэлний танин мэдэхүйн онолын талаар эргэцүүлэх нь: Review of a chapter in cognitive theories of bilingualism - G., Chuluun-Erdene (Mongolian Journal of Foreign Languages and Cultures, 2023)
This chapter forms a key part of a book by Colin Baker, Foundations of Bilingual Education and Bilingualism. It has long been assumed that children who have to learn in two languages are at a disadvantage. However, the whole thrust of this book – a massive 498 pages – is to demonstrate that educating children in two languages is, on the contrary, highly advantageous for them in terms of brain development, understanding language and developing all kinds of skills that are required in a modern society. This chapter is in some ways pivotal to that argument. Having gone exhaustively through many complicated theories of bilingualism development (usually from E Cummins but not always) Baker shows how academic studies confirm what every practised teacher knows anyway: that being adequately bilingual doesn’t diminish thinking or use of language in the other tongue – it in fact enhances it. This makes sense because learning a second language well, forces a person to think about structure, grammar and usage – skills that carry over to the first language.